Pediatric parotid gland tumors: Evaluation of 33 cases - Tunc, Orhan; Gonuldas, Burhanettin; Kanlikama, Muzaffer (Annals of Medical Research, 2021)
Aim: Diagnosis and treatment of parotid gland tumors is a problem for clinicians and pathologists because these tumors are rare in children. We aimed to contribute to the literature by retrospectively evaluating 33 patients that we operated for a parotid tumor in our clinic.Materials and Methods: Thirty-three pediatric patients operated from parotid gland tumor in the otolaryngology department between 2000-2019 were included in the study. All patients in the study were under the age of 18. Clinicopathologic data of pediatric parotid gland tumors were reviewed including age, sex, results of histopathologic tumor examination and surgical procedures.Results: Patient group consists of 25 (76%) males and 8 females (24%). The age range of the patients is between 1-18 and the average age is 10,6. Benign tumors were observed in 28 patients (85%) and malignant tumors in 5 patients (15%). The most common benign parotid gland tumor was Pleomorphic Adenoma. Among malignant tumors, adenoid cystic carcinoma was observed in 2 patients, mucoepidermoid carcinoma in 2 patients, and acinic cell tumor in 1 patient.Conclusions: Parotid gland tumors are rare in the pediatric age group, so it is difficult to manage. It should be aimed to apply the appropriate treatment in which every patient has the least risk of complications. Studies with much more patients about pediatric parotid tumors need to be done to further contribute to the literature.